ENVIRONMENTAL AND NON ENVIRONMENTAL ASPECTS INFLUENCE ON CARBON EMISSION DISCLOSURE IN COMPANIES LISTED ON IDX CARBON - Prameswari, Dolly Adolina; Sari, Martdian Ratna (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2025)
This study aims to analyze the relationship between environmental aspects (environmental performance and sustainability committee) and non-environmental aspects (company age, profitability, and media exposure) with carbon emission disclosure in companies listed on the Indonesian Carbon Exchange (IDXCarbon). This research is a quantitative study and the data used in this study are secondary data from financial reports, annual reports, and sustainability reports over five years (2018-2022) listed on the Indonesian Carbon Exchange (IDXCarbon). The results of this study indicate that both environmental and non-environmental aspects have an influence on the spread of carbon emissions, with the greatest impact coming from the existence of a committee that is willing in the company and the existence of media exposure that encourages companies to carry out dissemination to have an impact on the company's reputation. The practical implications of the results of this study are that it is important for companies that have not yet made disclosures to disclose carbon emissions in their company performance information immediately. In addition, in disclosing carbon emissions, it is necessary to consider forming a sustainability committee within the company so that the company's strategy related to environmental issues can have a positive impact on the company. Research related to the closure of carbon emissions is still interesting to do, especially focusing on environmental aspects and non-environmental aspects that will affect the closure, moreover, this study will use companies listed on the Indonesian carbon exchange to be able to provide a comprehensive picture of companies that have made disclosures. This research is expected to provide practical contributions related to environmental and non-environmental aspects that can be considered and become a major concern for companies that have not disclosed carbon emissions.